Implementasi Metode Scrum dalam Pengembangan Test Engine Try Out Sertifikasi - Siti Sauda; Nia Oktaviani; Muhammad Bunyamin (UIN Sunan Kalijaga Yogyakarta, 2019)
Bina Darma University is one of higher education under the auspices of the Region II Higher Education Service Institute committed to producing graduates who have competence. One tangible form that can see from the activities carried out through the Faculty of Computer Science is the capacity-building and capabilities of prospective graduates through the certification program. Available certifications are competency certifications from world-renowned vendors that have licenses to issue certifications. But the problem that occurs is the failure caused by the unfamiliarity of participants in seeing the types of issues to be faced. Even though if it is seen to take a vendor certification exam, it will cost a lot of money and time is not small. For that reason, in this research, an alternative solution was made, namely by making a test engine try out certification. In the process of developing a test engine, the Scrum method is used, which focuses on speed in development. the results of the event show that the test engine produced can function properly and can be used as a try out the tool before conducting a certification exam.Universitas Bina Darma merupakan salah satu penyelenggara pendidikan tinggi di bawah naungan Lembaga Layanan Pendidikan Tinggi Wilayah II berkomitmen untuk menghasilkan lulusan yang memiliki kompetensi. Salah satu wujud nyata yaitu dapat dilihat dari kegiatan yang dilakukan melalui Fakultas Ilmu Komputer yaitu kegiatan peningkatan kapasitas dan kapabilitas calon lulusan melalui program sertifikasi. Sertifikasi yang tersedia merupakan sertifikasi kompetensi dari vendor ternama dunia yang memiliki lisensi untuk mengeluarkan sertifikasi. Namun permasalah yang terjadi yaitu kegagalan yang disebabkan kurang terbiasanya peserta dalam melihat jenis soal-soal yang akan dihadapi. Padahal jika dilihat untuk mengikuti ujian sertifikasi vendor membutuhkan biaya yang mahal serta waktu yang tidak sedikit. Untuk itu didalam peneltian ini dilakukan upaya alternative solusi yaitu dengan dibuat test engine try out sertifikasi. Dalam proses pengembangan test engine digunakan metode Scrum yang berfokus pada kecepatan dalam pengembangan. hasil pengembangan menunjukkan bahwa test engine yang dihasilkan dapat berfungsi dengan baik serta dapat dijadikan sebagai alat try out sebelum dilakukannya ujian sertifikasi.